Instruments financed by the regional policy - Soboń, Janusz; Szewczyk, Roman (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2010)
The article describes the impact of financial integration on regional policies, instruments and types of financial instruments from the previous and current programming period in order to promote Polish regional policy